5+3s-2=8s+3-4s

Simple and best practice solution for 5+3s-2=8s+3-4s equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5+3s-2=8s+3-4s equation:


Simplifying
5 + 3s + -2 = 8s + 3 + -4s

Reorder the terms:
5 + -2 + 3s = 8s + 3 + -4s

Combine like terms: 5 + -2 = 3
3 + 3s = 8s + 3 + -4s

Reorder the terms:
3 + 3s = 3 + 8s + -4s

Combine like terms: 8s + -4s = 4s
3 + 3s = 3 + 4s

Add '-3' to each side of the equation.
3 + -3 + 3s = 3 + -3 + 4s

Combine like terms: 3 + -3 = 0
0 + 3s = 3 + -3 + 4s
3s = 3 + -3 + 4s

Combine like terms: 3 + -3 = 0
3s = 0 + 4s
3s = 4s

Solving
3s = 4s

Solving for variable 's'.

Move all terms containing s to the left, all other terms to the right.

Add '-4s' to each side of the equation.
3s + -4s = 4s + -4s

Combine like terms: 3s + -4s = -1s
-1s = 4s + -4s

Combine like terms: 4s + -4s = 0
-1s = 0

Divide each side by '-1'.
s = 0

Simplifying
s = 0

See similar equations:

| (3x+19/5)+(x+47/6)=17 | | (2/17)x=10 | | 3x-3.5=6.4x-16.42 | | 2t+7t=45 | | 7.79=2(3.14*r) | | (8-5i)(8-5i)= | | -(5y+5)-(-4y-6)=-3 | | 7.3x-8=6.3x+1 | | y/20=-26 | | 3(2x-1)+5=13 | | a=1/2(18*24) | | 1/6x=39 | | 17-3x=2x-2 | | 786=x+34+4(x-40) | | 8x5/9 | | -4(2b+3)+(9b-7)=0 | | 5(4x-6)-19x=7 | | 4x+1=2(x-7) | | b+8b-22=0 | | 3.5q-3.7-5.8q=-3.3q-3.9 | | 6y+5=5y-3 | | (21/25)(10/117)(27/14) | | 13-2/3x=3 | | 384-1/12 | | (8m-8m-27)(8m-25m-14)=0 | | .3(y)+.14(x)=.18 | | x+4x=58 | | -(3/5)x=(2/5) | | F(9)=100x-5 | | 5x/6-y/3=6 | | 19m=40-17.95 | | 36m^2-49/16=0 |

Equations solver categories